(untitled) (Journal of Universal Science Research, 2023)
Many studies in language learning have stated that the influence of listening skills in EFL classroom. This paper discusses the importance of listening comprehension. There are major reasons for acquiring a knowledge of relationship between listening comprehension and language learning. Listening skills play a vital role in learning English as they contribute to comprehension, communication abilities, pronunciation improvement, vocabulary expansion, cultural understanding, test preparation success, and self-study opportunities. Therefore, it is crucial for English learners to actively practice and develop their listening skills to enhance their overall language proficiency.